Low seed viability of a rare aster - Handley, Joy; Tronstad, Lusha (Journal of Pollination Ecology, 2024)
The reproductive ecology of rare plants is often unknown, yet the persistence of most plant populations depends on successful interactions with pollinators and favourable environmental conditions. Sexual reproduction maintains genetic diversity within plant populations using pollinators to transport pollen grains among plants of the same species and producing seeds. We investigated the reproduction of Yermo xanthocephalus Dorn (Desert yellowhead), a perennial member of Asteraceae endemic to central Wyoming, USA, which grows in only two locations within 8 km of each other. Our objectives were to assess the pollination and seed-set of Y. xanthocephalus. We conducted seed-set experiments in both populations to measure self-pollination and estimate if pollinating insects limited seed production. We used vane traps and pan traps to capture pollinators, and we examined pollen carried on bees. Yermo xanthocephalus can self-pollinate, but seed-set was extremely low. The number of viable seeds produced in flowerheads pollinated by insects did not differ from those produced by capitula hand-pollinated with excess pollen, indicating that pollinators did not limit seed production that year. Pollen from Y. xanthocephalus was carried by nine bee genera, suggesting that no one specific insect pollinates this plant. Only 12% of ovules produced viable seeds in the main population and 0% were viable in the other population, suggesting that something beyond pollinators limited seed-set. We recommend continued research to address what is limiting seed production to advance the knowledge and management of this declining plant species.